Effect of the Solvent Ratio (Ethylene Glycol/Water) on the Preparation of an Iron Sulfide Electrocatalyst and Its Activity towards Overall Water Splitting. Issue 12 (26th June 2019) - Shit, Subhasis; Jang, Wooree; Bolar, Saikat; Murmu, Naresh Chandra; Koo, Hyeyoung; Kuila, Tapas
Abstract: The polyol method is an efficient procedure for metal sulfide preparation where polyol not only acts as a solvent but also as reducing and morphology‐modulating agent. Herein, iron sulfide particles were prepared via a modified polyol method by changing the ethylene glycol (EG) : water (H2 O) ratio in the mixed solvent. Analytical techniques and electronic microscopy studies confirmed that the change in EG : H2 O ratio modulated the crystal structure, morphology, and electronic structure of the prepared iron sulfide particles. The electrocatalytic activity of iron sulfide changed owing to these modulations. EG helped in the formation of a sheet‐like structure – a morphology that favours a higher accessibility to the catalytically active sites. As evidenced form electrochemical impedance studies, an increased electron density near the Fermi level, a faster substrate adsorption‐desorption rate at the active sites, and a faster charge transfer at the electrode‐electrolyte interface were the key factors for the amplification in catalytic activity. The prepared iron sulfide particles showed an overall water splitting efficiency that is comparable to that of the state‐of‐the‐art RuO2 ‐Pt/C couple in alkaline medium. This study shows the potential of the polyol method in the preparation and catalytic‐activity modulation of Fe−S‐based electrocatalysts. Abstract : A change in the amount of ethylene glycol during the synthesis of iron sulfide via the polyol method can modulate the morphology and electron density near the Fermi‐energy level. These changes help to augment the charge transfer and substrate adsorption‐desorption at the semiconductor‐electrolyte junction, which in turn emphasises the electrocatalytic activity of iron sulfide.